1990
DOI: 10.1111/j.1399-6576.1990.tb03186.x
|View full text |Cite
|
Sign up to set email alerts
|

Speed of reversal of midazolam‐induced respiratory depression by flumazenil ‐ a study in patients undergoing upper G.I. endoscopy

Abstract: Intravenous midazolam was given to 17 patients coming to upper G.I. endoscopy. All patients had an ear oximeter and calibrated induction plethysmograph attached to record oxygen saturation and minute volume continuously. Midazolam induced significant depression of respiration. Following removal of the endoscope, a new base line was obtained before giving intravenous flumazenil in an attempt to reverse the sedative and ventilatory effects of midazolam. When 0.5 mg of flumazenil was given over 20 s, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 23 publications
0
12
1
1
Order By: Relevance
“…29 In contrast, we found that flumazenil was effective in reversing some components of midazolam-induced ventilatory depression (e.g., the decrease in VT). Analogous to the finding of Gross et al, t4 flumazenil did not reverse the depressant effects of midazolam on the CO2 response curve.…”
Section: Discussioncontrasting
confidence: 48%
“…29 In contrast, we found that flumazenil was effective in reversing some components of midazolam-induced ventilatory depression (e.g., the decrease in VT). Analogous to the finding of Gross et al, t4 flumazenil did not reverse the depressant effects of midazolam on the CO2 response curve.…”
Section: Discussioncontrasting
confidence: 48%
“…The antagonistic effect for respiratory depression induced by midazolam appears within 120 s after the i.v. injection of flumazenil, which immediately attenuates or eliminates respiratory depression . The underlying problem in using flumazenil is that re‐sedation may occur because this drug has a shorter duration of action than midazolam.…”
Section: Statements On Sedation In Gastroenterological Endoscopymentioning
confidence: 99%
“…The underlying problem in using flumazenil is that re‐sedation may occur because this drug has a shorter duration of action than midazolam. Because of the above mechanism, patients may awaken temporarily and then spontaneously lose consciousness again . A study compared flumazenil and a placebo given immediately and 30 min after the examination in 50 cases undergoing upper GI endoscopy under sedation with midazolam.…”
Section: Statements On Sedation In Gastroenterological Endoscopymentioning
confidence: 99%
See 2 more Smart Citations